The Transformation of Muslim Education in the Philippines: A Revisit - Gamon, Alizaman D.; Tagoranao, Mariam S. (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
Given the influence of secularism in interpreting social facts, the present study highlights the relevance of recognising cultural convergence as the ultimate panacea to the decades of unresolved conflicts amongst various cultural groups in the Philippines. The study underlines that the surviving epistemological foundation between two opposing cultures of knowledge must be taken as the point of reference in resolving historical injustices done to the Muslim communities. The transformation of Muslim education through government policy interventions and meaningful collaborations with Muslim leaders and scholars may provide a holistic framework for enhancing social and knowledge integration, particularly in the Bangsamoro Autonomous Region in Muslim Mindanao (BARMM). As such, the present study does not intend to provide a comprehensive revision of historical accounts about Islam in the Philippines; instead, it proposes an alternative approach in writing a history of Muslim education by embracing the universal principles that shape human culture and civilisation. Framed from the national agenda for social integration via education, the study views the prominence of systematic narration of the past events that captured the characteristics of Muslim communities, whose system of life and governance is based on advanced culture and civilisation is shaped by tawhidic worldview. In addition, the study maintains that drifting away from humanities and civilisational studies, which aims to restore values, ethics, morality, and vitality to a system of knowledge, will certainly result in losing the essence of education. Therefore, historians of education need to get up to speed to educate and inform people of the values necessary for understanding the existence of others. The methodology of the study is qualitative. It relies on primary and secondary sources on the history of Muslim education in the Philippines, government documents regarding policies in addressing the problem of Muslims in the Philippines, unpublished works, and interviews in addition to library research. The study recommends that historians of education should embrace the true principle of cultural convergence. Such profound recognition of ‘others’ and ‘us’ via the history of education may be achieved through inclusivity and open-minded outlooks, which recognises that BARMM is plural and a diverse community that is mutually connected with the universal teachings of Islam as religion, which encompasses culture, and civilisation.